Soft Skills are Important in Doctoral Degree Program: A Reflection by Doctoral Students - Rathi, Dinesh; Branch-Mueller, Jennifer (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2025)
Doctoral students need both hard skills (i.e., technical skills) and soft skills (i.e., social skills) to manage their learning journey and to succeed in their program of study. The paper presents findings from a qualitative study conducted with doctoral students enrolled in one of the Canadian U15 universities and studying in diverse doctoral degree programs. The study presents findings from the experiential reflection of doctoral students on the use of soft skills to succeed in their program of study. The participating students suggested a range of “non-academic” skills (i.e., soft skills) that were important in their learning journey such as communication, time management, conflict management, stress management, expectation management, work ethics, self- discipline and motivation, power navigation and others. This research aims to identify a wide range of soft skills that doctoral students need to move successfully in their program of study and contribute to the growing body of literature in the area of soft skills, particularly in the context of doctoral students and their programs. Les compétences relationnelles en contexte d'études doctorales : Une réflexion par des étudiants au doctorat Résumé Les étudiants au doctorat ont besoin à la fois de connaissances spécialisées et de compétences relationnelles pendant leur programme d'étude. Une étude qualitative a été faite auprès d'étudiants au doctorat dans une des universités canadiennes U15. Les résultats présentés dans cette affiche sont la réflection expérientielle d'étudiants au doctorat. Les étudiants au doctorat participants ont laissé entendre qu'ils avaient besoin d'une variété de compétences relationnelles, incluant la communication, la gestion du temps, la gestion des conflits, la gestion du stress, la gestion des attentes, l'éthique de travail, la discipline, la navigation du pouvoir, la motivation intrinsèque, ainsi que d'autres compétences. Cette étude vise à contribuer au nombre grandissant de littérature portant sur les compétences relationnelles plus précisément appliquée au contexte des étudiants au doctorat et le besoin pour diverses compétences relationnelles dans leur parcours d'apprentissage. Mots-clés compétences relationnelles; étudiants au doctorat; milieu universitaire; programme de doctorat